Innovative Tourism Sustainability: Case Study of Three Thematic Villages in Semarang City - Shinta Permana Putri Putri (PERSPEKTIF, 2025)
This study aims to identify supporting and inhibiting factors for the sustainability of thematic villages as one of the innovative tourism implementation programs in Semarang City. This study is qualitative. Data were collected through interviews with thematic village managers in Semarang City. This study was conducted in three thematic villages selected because of their categories as leading thematic villages with different products and representing various areas in Semarang City. Content analysis was used as an analysis technique in this study. The findings of this study indicate that several factors can support or inhibit the sustainability of thematic villages in Semarang City after the COVID-19 pandemic. Some of these supporting factors include the role of the community (i), informal networks (ii), Government assistance (iii), utilization of technology (iv), the ability to create new job opportunities (v), and product innovation/expansion (vi). In addition, several factors that can inhibit the sustainability of thematic villages include the number of visits (i), community initiation (ii), a sense of shared ownership (iii), involvement of related stakeholders (iv) and the younger generation (v), and management (vi). These results can be a reference for the Semarang City Government to develop sustainable thematic villages post-COVID-19 by considering the supporting and inhibiting factors successfully identified through this study.